Frekuensi “Ngemil”, Konsumsi Junk Food dan Screen Time dengan Kejadian Overweight pada Mahasiswa - M. Ikhsan Amar; Sulistyani Meita Dewi (Sarana Ilmu Indonesia (salnesia), 2021)
Adolescents who experience nutritional status are more due to the behavior of eating a lot but not doing physical activity so what happens is that the energy that enters the body is not appropriate and far more than the energy used for activity and growth. The purpose of this study was to determine the relationship between Frequency of